E-commerce na EJA: instrumento de prática social, estimulando a construção de significados para motivar uma cultura digital consciente - Araújo, Cléber Lemos de (2014)
This research analyzes the extent to which reflection on culture and on Cultural Industry enables students of the Youth and Adult Education - EJA be consciously included in the virtual space, but also checks the extent to which this contributes to social action letter them digitally, providing E-commerce as a pedagogical device. We discuss the possibility of generating culture and construction of meanings from the professor of social action, while it promotes a teaching contextualized with the literacy practices and digital literacy through E-commerce: MercadoLivre. Data were collected through questionnaires and interviews and allowed us to prove that you can use the E-commerce: MercadoLivre as a pedagogical device with a view to digital literacy. In this sense, we see, also, the occurrence of construction of meaning by students through the teacher's social action using this device, aiming to contribute to a digital inclusion or, on the other hand, although in one case or another does not promote inclusion digital students, promote the generation of culture.